2019
DOI: 10.3892/ijmm.2019.4110
|View full text |Cite
|
Sign up to set email alerts
|

Physalis peruviana L. inhibits ovalbumin‑induced airway inflammation by attenuating the activation of NF‑κB and inflammatory molecules

Abstract: Physalis peruviana L. (PP) is well known for its various properties, including its antioxidant property. In our previous study, the protective effects of PP against cigarette smoke-induced airway inflammation were confirmed. The purpose of the present study was to evaluate the anti-inflammatory effect of PP against ovalbumin (OVA)-induced airway inflammation. Treatment with PP inhibited the numbers of eosinophils and the levels of inflammatory cytokines, including interleukin (IL)-4, IL-5 and IL-13, in the bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Healthy female BALB/c mice (n=30, 6 weeks old; body weight, 16-18 g) were purchased from Koatech Co., Ltd., and used after 1 week of acclimatization with free access to food and water in specific pathogen-free conditions (22-23°C; 55-60% humidity; 12-h light/dark cycle). The experimental procedure was performed according to the methods described by Park et al (21). Briefly, the mice were sensitized twice intraperitoneally on day 0 and 14 with 30 µ g OVA and 3 mg Alums (Thermo Fisher Scientific, Inc.) dissolved in a solution of 0.2 ml PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Healthy female BALB/c mice (n=30, 6 weeks old; body weight, 16-18 g) were purchased from Koatech Co., Ltd., and used after 1 week of acclimatization with free access to food and water in specific pathogen-free conditions (22-23°C; 55-60% humidity; 12-h light/dark cycle). The experimental procedure was performed according to the methods described by Park et al (21). Briefly, the mice were sensitized twice intraperitoneally on day 0 and 14 with 30 µ g OVA and 3 mg Alums (Thermo Fisher Scientific, Inc.) dissolved in a solution of 0.2 ml PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Sun et al have demonstrated that metformin, which is used for the treatment of diabetes type 2, reduces lipopolysaccharide-induced damage to bronchial epithelial cells by suppressing NF-κB signaling [74]. The inhibition of the NF-κB signaling pathway is associated with the antiinflammatory effect of Physalis peruvianaL., used in the model of allergic asthma in animals [75]. It is apparent that the study of NF-κB functions is necessary to search for new therapeutic approaches in asthma.…”
Section: Ppar-dependent Mechanisms In Asthmamentioning
confidence: 99%
“…Plant extracts have been shown to exert protective effects against acute or chronic inflammatory lung diseases [ 16 - 18 ]. Lagerstroemia ovalifolia Teijsm.…”
Section: Introductionmentioning
confidence: 99%